Worming out the truth. (Economist, 2000)
The attack on Microsoft's corporate network in late 2000 remains a mystery, and the fact that Microsoft's source code may have been seen by a hacker raises security concerns. The attacker is believed to have used a virus called QAZ that first appeared in China in July 2000 and is known as a “Worm.” It can spread through the network and is launched when a PC user opens an e-mail attachment containing the malicious code. The hacker's identity is still unknown, but the case raises concerns over the safety of computer networks worldwide.